Analisis Pengaruh Variasi Putaran Mesin Roll terhadap Hasil Pengerolan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The rolling process is a material forming method that is greatly influenced by the roll rotation speed parameter. Inappropriate rotation variations can cause various defects such as waves, tears, thickness irregularities, and ovalization. This review aims to compare the effect of variations in the roll machine rotation speed on the quality of rolling results on various types of materials, including Al6061-O aluminum plate, rubber sheets, and hollow and pipe-shaped materials. The method used is a literature study by collecting and comparing data on roll speed, defects that appear, deformation results, and process efficiency from several relevant journals. The results of the analysis show that high rotation speeds increase productivity but also increase the risk of defects because the material does not have time to adapt to deformation. Conversely, low rotation speeds produce more stable shapes and minimize defects, but are less efficient for mass production. Each material has a different optimal rotation range, including 23–36 rpm for Al6061-O plate, 45–72 rpm for rubber sheet formation, 24.4 rpm for hollow and pipe rolling, and around 21 rpm for corrugated plate. Overall, this study confirms that rotational speed control is a critical factor in achieving a balance between deformation quality and machining efficiency.